Children with HbSβ0 thalassemia have higher hemoglobin levels and lower incidence rate of acute chest syndrome compared to children with HbSS. Issue 11 (9th August 2018) - Day, Melissa E.; Rodeghier, Mark; DeBaun, Michael R.
Abstract: Background: Based on the presumed clinical similarity between the two most severe sickle cell disease (SCD) genotypes, hemoglobin (Hb) Sβ 0 thalassemia and HbSS, randomized controlled trials (RCTs) have included both genotypes. Our group has demonstrated that healthcare providers inadequately distinguish the two diagnoses through clinical and laboratory parameters. Procedure: In a retrospective cohort study utilizing data from the Silent Cerebral Infarct Transfusion trial (NCT00072761), we tested the hypothesis that children with genotypic diagnoses of HbSβ 0 thalassemia, when compared to HbSS, have significantly different rates of SCD comorbidities. Exclusion criteria included those with previous overt stroke or treatment with hydroxyurea or regular blood transfusion therapy. Results: Among children with HbSβ 0 thalassemia (n = 22) and HbSS (n = 786), the mean hemoglobin was higher in children with HbSβ 0 thalassemia (9.2 g/dl) compared to HbSS (8.1 g/dl, P  < 0.001). In children with HbSβ 0 thalassemia, when compared to HbSS, the incidence rate of acute chest syndrome (ACS) was 3.0 and 14.4 events per 100 patient‐years ( P  = 0.028), and mean transcranial Doppler (TCD) velocities were 112.6 and 135.6 cm/sec, respectively ( P  = 0.026). The number of children with HbSβ 0 thalassemia and HbSS with conditional TCD velocities were zero (0%) and 26 (4.9%), respectively ( P  = 1.00), and the number with silent cerebral infarcts were five (27.8%) and 209 (30.8%), respectively ( P  = 0.78). Conclusions: We have provided preliminary evidence that clinically relevant differences occur in ACS rates and TCD velocities between children with HbSβ 0 thalassemia and HbSS. Future SCD RCTs should consider balanced allocation of these SCD genotypes, particularly when ACS and abnormal TCD velocities are primary outcome measures.